2010
DOI: 10.2353/ajpath.2010.091125
|View full text |Cite
|
Sign up to set email alerts
|

Wnt/β-Catenin Pathway Activation Is Enriched in Basal-Like Breast Cancers and Predicts Poor Outcome

Abstract: Although Wnt/beta-catenin pathway activation has been implicated in mouse models of breast cancer, there is contradictory evidence regarding its importance in human breast cancer. In this study, invasive and in situ breast cancer tissue microarrays containing luminal A, luminal B, human epidermal growth factor receptor 2 (HER2)(+)/ER(-) and basal-like breast cancers were analyzed for beta-catenin subcellular localization. We demonstrate that nuclear and cytosolic accumulation of beta-catenin, a read-out of Wnt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

18
403
2
4

Year Published

2010
2010
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 477 publications
(438 citation statements)
references
References 46 publications
18
403
2
4
Order By: Relevance
“…Other alterations such as Wnt pathway activation has been observed in BLBC [24]. This study reported cytoplasmic and nuclear accumulation of -catenin in BLBC, and suggested that β-catenin could be a valuable therapeutic target for this subtype [24].…”
Section: Molecular Profile Of Blbcsupporting
confidence: 51%
See 1 more Smart Citation
“…Other alterations such as Wnt pathway activation has been observed in BLBC [24]. This study reported cytoplasmic and nuclear accumulation of -catenin in BLBC, and suggested that β-catenin could be a valuable therapeutic target for this subtype [24].…”
Section: Molecular Profile Of Blbcsupporting
confidence: 51%
“…This study reported cytoplasmic and nuclear accumulation of -catenin in BLBC, and suggested that β-catenin could be a valuable therapeutic target for this subtype [24]. Nevertheless there is strong evidence of stabilization of β-catenin protein in a majority of human breast tumors, and mouse model systems clearly demonstrate that activated Wnt signaling can promote mammary tumorigenesis [25].…”
Section: Molecular Profile Of Blbcmentioning
confidence: 72%
“…Alteration of molecular biological markers in tumor tissues has become an important part in predicting the prognosis of patients with BC and seemed more specific than markers currently used in clinical such as TNM stage, weight loss and lymph node metastasis. There are many reports about the prognostic significance of β-catenin in BC (Lin et al, 2000;Gillett et al, 2001;Lim and Lee, 2002;Chung et al, 2004;Dolled-Filhart et al, 2006;Nakopoulou et al, 2006;Park et al, 2007;Fanelli et al, 2008;Paredes et al, 2008;Khramtsov et al, 2010;Kim et al, 2010;Logullo et al, 2010;Lopez-Knowles et al, 2010;Geyer et al, 2011;Cheng et al, 2012;Mukherjee et al, 2012;Xu et al, 2012;Ho et al, 2013;Pang et al, 2013;Weissenbacher et al, 2013;Li et al, 2014). However, results were inconsistent.…”
Section: Sensitivity Analysismentioning
confidence: 99%
“…Basal-like cancers also demonstrate some overlap with triple-negative cancers [4]. Different subtypes can be distinguished molecularly by gene expression signatures, such as expression of cytokeratins 5, 6, and 14 by basal-like cancers, and expression of cytokeratins 8 and 18 by luminal cancers [5, 8]. Other minor classifications, such as the claudin lo and claudin hi subgroups, have been identified, but their clinical significance remains to be determined [9].…”
Section: Overviewmentioning
confidence: 99%
“…Moreover, an understanding of these origins may provide insight into classification of cancer and may allow for better prognosis assessment [54]. Further complicating these ideas is that, within each tissue type, there may be particular cellular subtypes that give rise to stem-like tumor cells, such as the basal-like subgroup of breast cancer [5]. Basal-like breast cancers have been found to demonstrate aberrant activation of the canonical Wnt pathway, and Wnt signaling is a critical intracellular signal transduction pathway in stem cell biology [5].…”
Section: Stem-like Basis For Human Malignanciesmentioning
confidence: 99%